Centres and Peripheries: Early-Modern British Writers in a European Context. (12th June 2020) - Stevenson, Jane
Abstract: The ESTC has privileged a view of Britain's early print culture focused on London, while making it hard to look at British contributions to continental print cultures. But there were readers in early-modern Britain who were acculturated elsewhere. Scots bought most of their books on the continent, preferring Latin or French to English, and published on the continent, bypassing London. In Britain as a whole, there are effectively three centres for British print culture, London, 'Rome' and 'Geneva'. The Netherlands printed for the English market, notably illicit bibles with Geneva notes, and particularly successful books were often issued there in Dutch or French, while British writers in Latin fed into continental literary fashions. Take-up of English literature as such was limited, partly because the Dutch did not admire English poetics. Most of what the Dutch translated from English was political or religious. Some English protestant writers were massively successful in translation, but translation into Dutch was almost always a first step from which their work was disseminated.